The leading themes of the Gospel of John - Vine, William Edwy, 1873-1949 (Glasgow, UK Pickering and Inglis)
Includes index.
Brethren writer. Written originally for inclusion in "The Witness". Copy 1 donated by The family of the late Mr R. Scanlan. Preface dated 1924.
Keywords: Bible. N.T. John -- criticism, interpretation, etc